2018
DOI: 10.1136/jmedgenet-2017-104744
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the MLH1 promoter region in 480 patients with colorectal cancer and 1150 controls reveals new variants including one with a heritable constitutional MLH1 epimutation

Abstract: We report the second promoter variant stably inducing a hereditary CEM. Concerning the classification of promoter variants, we discuss contradictory results from the literature for two variants, describe classification discrepancies between existing rules for five variants, suggest the (re-)classification of five promoter variants to (likely) benign and regard four variants as functionally unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…As for the rest, we lack conclusive information regarding the cause as well as the risk of potential transmission between parents and children. In this respect, apart from a higher incidence of constitutive methylation in the general population, current findings for BRCA1 methylation resemble previous findings for MLH1 methylation and the risk of colorectal cancer [ 13 , 14 ].…”
supporting
confidence: 86%
“…As for the rest, we lack conclusive information regarding the cause as well as the risk of potential transmission between parents and children. In this respect, apart from a higher incidence of constitutive methylation in the general population, current findings for BRCA1 methylation resemble previous findings for MLH1 methylation and the risk of colorectal cancer [ 13 , 14 ].…”
supporting
confidence: 86%
“…In order to rule out the presence of regulatory sequence variants that might determine a cis -acting effect on promoter methylation and gene silencing, we performed Sanger sequencing of the BRCA1 5′-UTR, which confirmed the absence of variants in the 500 bp upstream of the translation starting site. This phenomenon, usually underlying heritable constitutional epimutations rather than sporadic methylation events, is well characterized for mismatch repair genes [34], and has been recently described for BRCA1 by Evans et al, who reported a co-segregation of the c.-107A>T variant with BRCA1 promoter methylation and gene silencing in multiple affected individuals of two families from North West England [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, about 5%-15% of colorectal carcinomas (CRCs) display reduced MLH1 immunostaining and MMR deficiency due to promoter hypermethylation. In most cases, epigenetic inactivation is a somatic event, but constitutional MLH1 hypermethylation has been reported in several patients [125][126][127][128]. Overall, this mechanism explains 1.5%-10.5% of CRCs associated with abnormal expression of MLH1, and might account for up to 3% of LS [128].…”
Section: Lynch Syndromementioning
confidence: 99%